Cooperative and Financial Literacy on Cooperative Performance: The Mediating Role of Business Capability - Djuniardi, Dede; Karmela, Lili; Kartika, Neng Evi (MATRIK: JURNAL MANAJEMEN, STRATEGI BISNIS, DAN KEWIRAUSAHAAN, 2026)
The aim of this study is to examine how cooperative literacy, financial literacy, and business capability influence cooperative performance in Indonesia, with a focus on West Java, where performance remains relatively low due to suboptimal managerial competence.A questionnaire was used to gather data, and it yielded analyzable responses from 581 respondents consisting of chairperson, scretary and tresurer cooperatives in West Java. The entire data processing by SEMPLS with WarpPLS software.  This study finds that cooperative literacy, financial literacy and business capability have an impact on cooperative performance. Cooperative literacy has positive impact to business capability, but financial literacy is not. Then business capability can mediation to cooperative literacy but not for financial literacy. Cooperative management must improve their knowledge of cooperatives, financial management and business knowledge through training programs for cooperatives to flourish more effectively.